Analysis of Power Losses in Electric Distribution System Using a MATLAB-Based Graphical User Interface (GUI) (2019)
This paper describes a graphical user interface (GUI) developed in MATLAB that provides a user-friendly environment for analyzing the power loss behavior in distribution networks with radial configurations. This GUI allows power systems analysts an easier understanding of the effect of the power dissipation in conductors. The implementation of this GUI implements three radial test feeders using 10, 33 and 69 nodes. As power flow methodology, the successive approximation power flow method was employed. The proposed GUI interface allows identifying the power loss performance in the distribution networks by including a distributed generator (DG) into the grid, operating with unity power factor. This DG is connected to each node to determine which connection provides with the optimal power loss minimization. Numerical results supported by the graphical analysis validate the applicability and importance of user-friendly GUI interfaces for analyzing power systems. © 2019, Springer Nature Switzerland AG.